A New Route from Moral Disagreement to Moral Skepticism. Issue 2 (2019) - RISBERG, OLLE; TERSMAN, FOLKE
Abstract: Moral disagreement is sometimes thought to pose problems for moral realism because it shows that we cannot achieve knowledge of the moral facts the realists posit. In particular, it is 'fundamental' moral disagreement—that is, disagreement that is not due to distorting factors such as ignorance of relevant nonmoral facts, bad reasoning skills, or the like—that is supposed to generate skeptical implications. In this paper, we show that this version of the disagreement challenge is flawed as it stands. The reason is that the epistemic assumptions it requires are incompatible with the possibility of fundamental disagreement. However, we also present an alternative reconstruction of the challenge that avoids the problem. The challenge we present crucially invokes the principle that knowledge requires 'adherence'. While that requirement is usually not discussed in this context, we argue that it provides a promising explanation of why disagreement sometimes leads to skepticism.